A membrane-targeted photoswitch restores physiological ON/OFF responses to light in the degenerate retina - Gaia Ziraldo; Sara Cupini; Valentina Sesti; Emanuela Delfino; Guglielmo Lanzani; Chiara Bertarelli; Fabio Benfenati; Stefano Di Marco (Nature Communications)
Abstract The lack of effective therapies for visual restoration in Retinitis pigmentosa and macular degeneration has led to the development of new strategies, such as optogenetics and retinal prostheses. However, visual restoration is poor due to the massive light-evoked activation of retinal neurons, regardless of the segregation of visual information in ON and OFF channels, which is essential for contrast sensitivity and spatial resolution. Here, we show that Ziapin2, a membrane photoswitch that modulates neuronal capacitance and excitability in a light-dependent manner, is capable of reinstating, in mouse and rat genetic models of photoreceptor degeneration, brisk and sluggish ON, OFF, and ON-OFF responses in retinal ganglion cells evoked by full-field stimuli, with reactivation of their excitatory and inhibitory conductances. Intravitreally injected Ziapin2 in fully blind rd10 mice restores light-driven behavior and optomotor reflexes. The results indicate that Ziapin2 is a promising molecule for reinstating physiological visual responses in the late stages of retinal degeneration.